Blocking the FGF/FGFR system as a ⿿two-compartment⿿ antiangiogenic/antitumor approach in cancer therapy. (May 2016) - Giacomini, Arianna; Chiodelli, Paola; Matarazzo, Sara; Rusnati, Marco; Presta, Marco; Ronca, Roberto
Graphical abstract: Abstract: Fibroblast growth factors (FGFs) are a family of pleiotropic factors produced by stromal and parenchymal tumor cells. Even though FGFs have been firstly characterized as angiogenic factors, they exert autocrine and paracrine functions not only on endothelial cells but also on tumor cells and other stromal components. Thus, the FGF/FGF receptor (FGFR) pathway may represent a key player in tumor growth by regulating the complex cross-talk between stromal and tumor compartments. The ligand dependent or independent activation of the FGF/FGFR system by gene upregulation, oncogenic mutation or amplification occurs in a variety of human tumors and is implicated in various key steps of tumor growth and progression. In addition, FGF/FGFR activation has been described as a mechanism of tumor escape in response to antiangiogenic/anti-VEGF therapies. Experimental and clinical evidences provide a compelling biologic rationale for the development of anti-FGF/FGFR targeting agents in cancer therapy. However, the development of drugs specifically targeting the FGF/FGFR pathway proved to be difficult, also due to the high redundancy and pleiotropic effects of FGF and FGFR family members. On the other hand, the possibility to develop ⿿two-compartment⿿ targeting agents endowed with both antiangiogenic and antitumor activities remains promising. Here we will review the preclinical and clinical approaches and potential therapeutics currently available to block the FGF/FGFR system in human cancer.